Torrefaction, temperature, and heating rate dependencies of pyrolysis of coffee grounds: Its performances, bio-oils, and emissions. (February 2022) - Fu, Jiawei; Liu, Jingyong; Xu, Weijie; Chen, Zhibin; Evrendilek, Fatih; Sun, Shuiyu
Graphical abstract: Highlights: Pyrolysis performance and products of torrefied coffee grounds (CG) were compared. Kinetic parameters of control and torrefied CG were estimated. Torrefaction delayed the start and end times of the CG pyrolysis. Activation energy of pyrolysis of CG torrefied at 250 °C was lowest. CG torrefied at 300 °C reduced the hydrocarbon proportion of bio-oils. Abstract: The torrefaction pretreatment is of great significance to the efficient conversion of biomass residues into bioenergy. In this study, the effects of the three torrefaction temperatures (200, 250, and 300 °C) on the pyrolysis performance and products of coffee grounds (CG) were quantified. The torrefaction treatment increased the initial devolatilization and maximum peak temperatures of the CG pyrolysis. Activation energy of CG250 was lower than that of CG and more conducive to the pyrolysis. Torrefaction altered the distributions of the pyrolytic products and promoted the generation of C=C. Torrefaction changed the composition ratio of the pyrolytic bio-oils although cyanoacetic acid and 2-butene still dominated the bio-oils. The joint optimization pointed to pyrolysis temperature > 600 °C and torrefaction temperature ≤ 270 °C as the optimal conditions. Our experimental results also verified that torrefaction of CG may be more suitable at 200 and 250 °C than 300 °C.